Questions of design of jet-droplet optical measuring systems: control of electrification of metallized polymer films during automated laser perforation - E. V. Leun; A. I. Cheredov; D. V. Sergeev; V. K. Sysoev (Омский научный вестник)
The article is devoted to the use of jet-droplet optical measuring systems (JDOMS) for monitoring the electrization of products such as metallized polymer films during their laser perforation. The article shows that the main reason for the electrization of films is the removal of matter by a laser pulse with the formation in the microvolume of the plasma, a gaseous ionizing substance and its partial deposition on the edge of the perforated hole in the absence of contact with the metallization of the film. The JDOMS operating mode with the formation of a monodisperse coherent controlled charged droplet flow and video recording of the trajectory of charged droplets along the centers of perforated holes near the film is described based on the measurements of which electrization is controlled. The maximum charges of the perforated holes of the film and moving drops are determined. The displacements from their interaction and the JDOMS sensitivity limit for electrification control are calculated. The requirements to the means of video recording and processing of the obtained stroboscopic micrographs are determined.